What Must We Know and Know How to Do for Implementation During the PENTA UC School Program? A View from the Teachers - Cabrera-Murcia, Elsa Piedad (2012)
This study explored what should be known, by a teacher of talented children, when implementing the PENTA UC School program. This study included a sample of 18 educators directly involved in the implementation process of this enrichment program. Teachers established bridges between verbalized knowledge and their pedagogic practice, recognizing know and know-how as two fundamental spheres of knowledge for the implementation of this program. The results show that these spheres traverse five different dimensions: planning, implementation, evaluation, learning environment, and collaborative work; which, in conjunction, allow the teacher to apply a differentiated instruction, taking into consideration the particular learning paces and characteristics of talented children. Furthermore, the need to consider these spheres in teacher’s preparation programs was confirmed.